Development of Interactive and Reflective Learning among Malaysian Online Distant Learners: An ESL Instructor’s Experience - Murugaiah, Puvaneswary; Thang, Siew Ming (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
Technology has brought tremendous advancements in online education, spurring transformations in online pedagogical practices. Online learning in the past was passive, using the traditional teacher-centred approach. However, with the tools available today, it can be active, collaborative, and meaningful. A well-developed task can impel learners to observe, to reflect, to strategize, and to plan their own learning. This paper describes an English as a Second Language (ESL) instructor’s attempt to foster interactive and reflective learning among distance learners at a public university in Malaysia, working within the framework proposed by Salmon (2004). The authors found that proper planning and close monitoring of a writing activity that incorporates interactive and reflective learning helped to raise the students’ awareness of their own learning process and consequently helped them to be more responsible for their learning. The students acquired significant cognitive benefits and also valuable practical learning skills through the online discussions. However, there were challenges in carrying out the writing task to promote this form of learning, including students’ professional and family commitments and cultural attitudes as well as communication barriers in the online environment. To overcome these challenges, the authors recommend the following: ensure tutor guidance, enforce compulsory participation, address technical problems quickly, commence strategic training prior to the beginning of a task, and implement team teaching with each instructor taking on certain roles.